PENGARUH HARGA DAN KEPERCAYAAN MERK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN GO-JEK - Farochi, Chomsun; Hidayat, Rahmat; Hidayat, Rahmat (Aksara Public, 2018)
Price is a company management system that will determine the appropriate basic price for the product or service and also need to determine strategies related to discounts, payment of freight costs, and various related variables. While a trusted brand is a brand reliability capability, based on consumer confidence that the product is able to meet the promised value and brand intentions based on consumer belief that the brand is able to prioritize the interests of consumers. Therefore, this study aims to determine whether the price and trusted brand effect on consumer purchasing decisions Go-Jek. In this study, researchers want to know how big these variables affect purchasing decisions. The results of this study indicate that there is a relationship between price and trusted brand to the purchase decision with F test results of 48.719 while F table can be seen by using f table with residual free degree (df) that is 97 as denominator and df regression is 3.94. Since F arithmetic (48.719)> F table (3.94) then H1 accepted. Based on the significance, visible column sig is 0,000 that means the probability of 0,000 <0.05 then H0 is rejected, then a significant difference between the price and the trusted brand on consumer purchasing decisions Go-Jek.